2011
DOI: 10.5205/reuol.1262-12560-1-le.0509201125
|View full text |Cite
|
Sign up to set email alerts
|

Nursing process and septic shock: intensive nursing care

Abstract: Objective: to employ the Nursing Process by using the International Classification for Nursing Practices (ICNP®) and the Campaign Guidelines Surviving to Sepsis. Method: descriptive research, of case study, which was evaluated by the Committee of Ethics in Research of the Lauro Wanderley University Hospital/UFPB according to CAAE number 0085.0.126.000-08, and carried out with a woman who was hospitalized in the General Intensive Care Unit of a school-hospital having been diagnosed with Septic Shock. The data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Studies have shown a prevalence ranging from 36% to 100% for the nursing diagnosis of impaired comfort in pregnant women and adult patients hospitalized in clinical and surgical units (Aksoy Derya & Pasinlioğlu, 2017; Frauenfelder et al, 2016; Frazen et al, 2012; Lopes et al, 2016; Santos et al, 2015). Studies investigating the clinical indicators of impaired comfort have found that anxiety and irritability were the most prevalent clinical indicators in a sample of trauma victims (Sallum & Sousa, 2012), while restlessness was the most prevalent clinical indicator in a diagnostic profile study carried out with psychiatric patients (Frauenfelder et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown a prevalence ranging from 36% to 100% for the nursing diagnosis of impaired comfort in pregnant women and adult patients hospitalized in clinical and surgical units (Aksoy Derya & Pasinlioğlu, 2017; Frauenfelder et al, 2016; Frazen et al, 2012; Lopes et al, 2016; Santos et al, 2015). Studies investigating the clinical indicators of impaired comfort have found that anxiety and irritability were the most prevalent clinical indicators in a sample of trauma victims (Sallum & Sousa, 2012), while restlessness was the most prevalent clinical indicator in a diagnostic profile study carried out with psychiatric patients (Frauenfelder et al, 2016).…”
Section: Introductionmentioning
confidence: 99%